Termite assemblages from oil palm agroecosystems across Riau Province, Sumatra, Indonesia - Saputra A.; Jalaludin N.-A.; Hazmi I.R.; Rahim F. (American Institute of Physics Inc., 2024)
Termite survey was conducted at six oil palm agroecosystem sites in Riau Province, Sumatra, Indonesia to document species richness across the sites. Six sites were surveyed by using continuous transect representing gradients of oil palm landuse across Indragiri Hulu to Bengkalis District since February 5th, 2015 until May 21st, 2015. Termites were sampled by modified transect protocols (100 m 4 m 10 cm). A total of 23 species belonging to two families and five subfamilies were collected. The termite assemblage was dominated by wood-feeding termites. The major family collected was Rhinotermitidae which included some pest species, such as Coptotermes curvignathus, C. sepangensis, C. kalshoveni, Schedorhinotermes malaccensis, S. medioobscurus, S. brevialatus, and S. javanicus. 2016 Author(s).